Strategies for Teaching Linguistic Preparedness for Physicians: Medical Spanish and Global Linguistic Competence in Undergraduate Medical Education - Norma P?rez (Mary Ann Liebert, 2019)
In accordance with Liaison Committee on Medical Education (LCME) curriculum content standards, medical schools are expected to teach physician communication skills and cultural competence. Given the sustained U.S. Spanish-speaking population growth, importance of language in diagnosis, and benefits of patient?physician language concordance, addressing LCME standards equitably should involve linguistic preparedness education. The authors present strategies for implementation of linguistic preparedness education in medical schools by discussing (1) examples of institutional approaches to dedicated medical Spanish courses that meet best practice guidelines and (2) a partnership model with medical interpreters to implement integrated global linguistic competencies in undergraduate medical curricula.